(untitled) (Research, Society and Development, 2020)
Pregnancy is a biological process that involves, in addition to the couple, family members, the community and the health professionals, who work during this period, accompanying from prenatal to the puerperium. Important period for all changes and resulting from pregnancy to occur smoothly. For the Ministry of Health, pregnancy is also an issue for men, stimulating the father’s participation during this process, interacting with the health team, is fundamental for the biopsychosocial well-being of the mother-baby binomial and of himself, and prenatal care is an opportune time for this. The study aims to identify paternal participation in prenatal care and women’s health as evidenced in scientific publications, analyzing factors that contribute to this participation, shown in scientific publications. This is an integrative literature review, the research was done through an online search in the bases: Coordination for the Improvement of Higher Education Personnel, Latin American and Caribbean Literature in Health Sciences and Scientific Electronic Library Online with the descriptors: Pregnancy, Fatherhood and Care Prenatal. The studies were grouped into two categories, according to their similarity: The father’s participation in prenatal care and the father’s participation in childbirth. Concluding that paternal participation in the monitoring of prenatal and childbirth is essential for the woman, due to the security and confidence that the pregnant woman feels to face all physical changes, thus being able to be a collaborator in promoting the health of the partner when pregnant, and helping to bring this family closer, thus bringing quality of life.